Long-Term Results of Angioplasty and Stent Placement for Treatment of Central Venous Obstruction in 126 Hemodialysis Patients: A 10-Year Single-Center Experience - Ozyer, Umut; Harman, Ali; Yildirim, Erkan; Aytekin, Cuneyt; Karakayali, Feza; Boyvat, Fatih (American journal of roentgenology (1976), 2009)
The objective of our study was to report and compare long-term results of percutaneous transluminal angioplasty and stenting of central venous obstruction in hemodialysis patients. Hemodialysis patients who underwent successful endovascular treatment of central venous obstruction were retrospectively evaluated. Stenotic lesions greater than 50% or inducing extremity swelling were subject to treatment. The primary treatment was angioplasty, and stent placement was accomplished in angioplasty-resistant obstructions. Angioplasty was the primary treatment of recurrence after stent placement. Additional stenting was reserved for angioplasty-resistant recurrences. One hundred forty-seven veins in 126 patients (63 males, 63 females) between 15 and 82 years old primarily underwent 101 angioplasties and 46 stent placements. The mean follow-up was 22.1 +/- 16.3 (SD) months. The average number of interventions per vein in the stent group (2.7 +/- 2.4 interventions) was significantly higher than that in the angioplasty group (1.5 +/- 1.0 interventions). Primary patency was significantly higher in the angioplasty group (mean, 24.5 +/- 1.7 months) than that in the stent group (mean, 13.4 +/- 2.0 months). Assisted primary patency of the angioplasty group (mean, 31.4 +/- 2.0 months) and that of the stent group (mean, 31.0 +/- 4.7 months) were equivalent. The overall mean primary patency was 21.1 +/- 1.4 months, and the overall mean assisted primary patency was 31.7 +/- 2.5 months. There were no significant differences in patency rates with regard to patient sex, the type of stent used, the vein or veins treated, or the type of lesions. Endovascular treatment of central venous obstruction is a safe and effective procedure in hemodialysis patients. Stenting has a significantly lower primary patency rate than angioplasty but adds to the longevity of vein patency in angioplasty-resistant lesions; therefore, stent placement should be considered in angioplasty-resistant lesions.